Предмет: Алгебра, автор: alimxolbaev07

Упростите выражения

Приложения:

Ответы

Автор ответа: 7x8
1

Ответ:

11. B)

12. C)

Объяснение:

\frac{x}{1-x}-\frac{1-x^2}{1+x^2}\cdot \left(\frac{1}{(x-1)^2}-\frac{x}{1-x^2}\right)=

\frac{x}{1-x}-\frac{1-x^2}{1+x^2}\cdot \left(\frac{1}{(1-x)^2}-\frac{x}{(1-x)(1+x)}\right)=

\frac{x}{1-x}-\frac{1-x^2}{1+x^2}\cdot \left(\frac{1+x}{(1-x)^2(1+x)}-\frac{(1-x)x}{(1-x)^2(1+x)}\right)=

\frac{x}{1-x}-\frac{(1-x)(1+x)}{1+x^2}\cdot\frac{1+x-(1-x)x}{(1-x)^2(1+x)}=

\frac{x}{1-x}-\frac{(1-x)(1+x)}{1+x^2}\cdot\frac{1+x-x+x^2}{(1-x)^2(1+x)}=

\frac{x}{1-x}-\frac{(1-x)(1+x)}{1+x^2}\cdot\frac{1+x^2}{(1-x)^2(1+x)}=

\frac{x}{1-x}-\frac{1}{1-x}=

\frac{x-1}{1-x}=\frac{-(-x+1)}{1-x}=-1

\frac{a^2+ab+b^2}{a^3-b^3}-\frac{a^2-ab+b^2}{a^3+b^3}=

\frac{a^2+ab+b^2}{(a - b)(a^2 + ab + b^2)}-\frac{a^2-ab+b^2}{(a + b)(a^2 - ab + b^2)}=

\frac{1}{a - b}-\frac{1}{a + b}=

\frac{a+b}{(a - b)(a+b)}-\frac{a-b}{(a-b)(a+b)}=

\frac{a+b-a+b}{(a-b)(a+b)}=

\frac{2b}{a^2-b^2}

Похожие вопросы